-(x-1)=x+1

Simple and best practice solution for -(x-1)=x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-1)=x+1 equation:


Simplifying
-1(x + -1) = x + 1

Reorder the terms:
-1(-1 + x) = x + 1
(-1 * -1 + x * -1) = x + 1
(1 + -1x) = x + 1

Reorder the terms:
1 + -1x = 1 + x

Add '-1' to each side of the equation.
1 + -1 + -1x = 1 + -1 + x

Combine like terms: 1 + -1 = 0
0 + -1x = 1 + -1 + x
-1x = 1 + -1 + x

Combine like terms: 1 + -1 = 0
-1x = 0 + x
-1x = x

Solving
-1x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1x + -1x = x + -1x

Combine like terms: -1x + -1x = -2x
-2x = x + -1x

Combine like terms: x + -1x = 0
-2x = 0

Divide each side by '-2'.
x = 0

Simplifying
x = 0

See similar equations:

| ((ln-5)/(ln3))-5 | | 1000x^3+7000x=18000 | | 9x+13=13(2x-4)+31 | | 3x+2yi=14-9i | | 17-6*x=47+10*x | | X-20x+2x+20=180 | | p-0.6*40=19 | | -17x=13x-28 | | 2-16t=6(-t+2) | | 6y+10=3y+y^2 | | 2x-1x+x+74=180 | | 16x+4=-4 | | (x-7)(x-2)(x-4)(x-5)=7x | | p-0.6*30=19 | | (5X^3+x^2+x-13)(x^2-1)= | | (2m-7n)(2m-3n)= | | -9(-2r-10s+3)= | | 2Inx-5Inx=6 | | 3x-1x+4x+13=180 | | 8(c-6)= | | (4x^2-6)(7x^2-7)= | | 5-3/2(6-2/3y) | | 13(x+5)= | | 3x+2=5x-18 | | y=3x^3-7x^2-14x+24 | | log5[5x/x-2]=2 | | 3b-5b=10 | | 3.25b-1.5=14.5 | | 3.25-1.5=14.5 | | 3(x-7)=63 | | Ln(x)=-90 | | 3(c-4)=3c-12 |

Equations solver categories